EZH2 orchestrates apicobasal polarity and neuroepithelial cell renewal. Issue 1 (1st January 2016) - Akizu, Naiara; Martínez-Balbás, Marian A.
ABSTRACT: During early stages of neural development, neuroepithelial cells translocate their nuclei along the apicobasal axis in a harmonized manner with the cell cycle. How cell cycle progression and neuroepithelium polarity are coordinated remains unclear. It has been proposed that developmental cues, epigenetic mechanisms and cell cycle regulators must be linked in order to orchestrate these processes. We have recently discovered that a master epigenetic factor, EZH2 is essential to coordinate these events. EZH2 directly represses the cell cycle regulator p21 WAF1/CIP in the chicken spinal cord. By doing so, EZH2 controls neural progenitor cell renewal and fine-tunes Rho signaling pathway, which is essential to maintain neuroepithelial structure. Our findings point to a new role of EZH2 during development that could have potential implication in other areas as cancer.